P295 The burden of opiates on functional dyspepsia (FD) patients referred to functional secondary care. (19th June 2022) - Isherwood, Grace; Lewis-Lawson, Tilly; Bush, Debbie; Card, Tim; Corsetti, Maura
Abstract : Introduction: There is a global opioid crisis and recent studies have demonstrated that many patients with functional GI disorders take opioids and these are associated with increased health-care utilisation. (Melchior C et al, Frontiers Pharmacol 2020; Sayuk GS et al, Aliment Pharmacol Ther 2018) As no data is available in the UK, the purpose of this study was to investigate the percentage of patients diagnosed with FD who take opioids, their symptomatology, healthcare use as compared to those not taking opioids and to explore whether opioid cessation proved beneficial. Methods: A retrospective clinical audit was undertaken, involving 202 patients with FD from a single Functional Gastroenterology Clinic from 2016-2021. Data on patient demographics, symptoms, previous investigations, medications and admissions was extracted from consultation letters and from hospital records. Patients were separated into two groups: opioid users and opioid free. They were statistically analysed via the Student T test and Fisher's exact test. Results: 31.7% of FD patients were taking opioids and they were older (47.8 Vs 41.3, P=0.006), presenting more frequently with nausea (79.7% Vs 62.3%, P=0.015), vomiting (59.4% Vs 31.2% P=0.0002), constipation (40.6% Vs 20.3%, P=0.0035) and changes in bowel habit (84.4% Vs 62.3%, P=0.0017) as compared with those not taking opioids. They were also on a significantly greater number of total medications (7.45 Vs 2.67, P<0.0001) and had significantly more total (6.91 Vs 2.33, P = 0.025) and GI related hospital admissions (2.89 Vs 1.05, P= 0.041). 67.5% of patients on opioids stopped taking them and of these, 55.6% experienced symptom improvement. Conclusion: Opioid use was prevalent amongst FD patients and was associated with an exacerbation of symptoms and increased utilisation of resources. The detrimental effect of opioids on FD patients needs to be recognised and addressed through implementation of policies to reduce opioid prescriptions.